ANTI GLUTAMIC ACID DECARBOXYLASE ANTIBODY MEDIATED ENCEPHALOPATHY WHILE ON ETANERCEPT IN A PATIENT WITH MULTIPLE AUTOIMMUNE DISEASES. Issue 11 (9th October 2013) - MacDougall, Niall; Waddell, Briony; O'Riordan, Jonathan I
Abstract : A 39 year old lady presented with an altered mental state and unsteadiness of gait. She had a history of juvenile idiopathic arthritis, autoimmune thyroiditis and alopecia, protein S deficiency with vena cava thrombosis, previous excision of ovarian mass and vasculitic rash. There was a previous history of ovarian mass and her immunomodulatory therapy for arthritis over the previous year was Etanercept. She used recreational cannabis but denied any other illicit drug usage. Her affect was variable and at times inappropriate with frequent laughter. She would spit regularly. There was anxiety and a prevailing sensation of doom. There was no clinical evidence of seizure activity. There were mild cerebellar signs with ataxia and gaze evoked nystagmus. Initial Addenbrooke's cognitive examination (ACE) revealed deficits predominantly in memory, fluency and language with an overall score of 47/100. Urine toxicology detected cannabis and nothing else. MRI demonstrated T2 hyperintensities in the cerebellum and left inferior cerebellar peduncle. CSF analysis revealed an elevated white cell count of 60 (90% lymphocytes, 10% polymorphs) and protein of 802mg/L. She was initially treated with acyclovir for presumed viral encephalitis although PCR was negative for HSV, varicella, enterovirus, JC virus and BK virus. EEG was unremarkable. Anti Glutamic Acid Decarboxylase (GAD) antibody was strongly positive at 13235 U/mL. Other antibodies including anti–NMDA, anti–voltage gated potassium channel, anti–CASPR2 and anti–Lgi–1 were negative. A presumptive diagnosis of autoimmune encephalopathy was made and she was treated with intravenous methylprednisolone followed by oral prednisolone. Etanercept was discontinued and Mycophenolate Mofitil initiated. Repeat ACE at 2 weeks was improved at 66/100 with higher scores for memory, fluency and language. Repeat lumbar puncture showed a CSF white cell count of 23 (100% lymphocytes) and a lower protein count (475 mg/L). The patient continued to improve cognitively and was allowed home from hospital 5 weeks after admission. By then her ACE score was 87/100 and her behaviour was normal. She was followed up in clinic 2 weeks later and a sustained recovery was noted. Anti–GAD encephalitis is one of a group of increasingly recognised autoimmune encepalitides. The antiobody is directed to an intracellular antigen and is not usually paraneoplastic. Our patient had multiple immune mediated illnesses, presented acutely and made a good recovery with immunosuppression. The incidence and prevalence of autoimmune encephalitides are uncertain but treatable conditions can be identified in many patients. The phenotype of anti–GAD encephalitis appears to be variable. Our case suggests that immunodulatory therapy with Etanercept may not be helpful in this scenario.